How Does Developing Enforcement Capacity Reduce Wildlife Crime? Increasing program effectiveness by understanding common assumptions - and Price, Claire; Buff, Jesse; Peabody, Shawn; Present, Tess; Lauck, Liz (USAID, 2018)
"How Does Developing Enforcement Capacity Reduce Wildlife Crime?" summarizes findings from the literature around four key assumptions about capacity building for enforcement and prosecution. Using the experiences and evidence summarized in this brief, program designers and implementing partners should be able to increase the effectiveness and efficiency of their capacity building efforts.